Health teaching-learning process in the scenario of digital information and communication technologies (Research, Society and Development, 2020)
This is an integrative literature review, with the purpose of highlighting and raising reflections on the main characteristics of the teaching-learning process in health using digital information and communication technologies (TDIC), based on scientific publications indexed in the database from the Biblioteca Virtual em Saúde (BVS) and MENDELEY between 2013 and 2017. Valuable results were found evidencing knowledge production and propagation through these technologies. Obstacles were also found to curb their full use. However, the results were perceived as satisfactory in the sphere of users, managers and health professionals. The TDIC presented itself as an excellent vehicle for the teaching-learning process.